Distribution of turbulent energy in combined wave current flow. (1st November 2018) - Raushan, Pankaj Kumar; Singh, Santosh Kumar; Debnath, Koustuv; Mukherjee, Manidipto; Mazumder, Bijoy S.
Abstract: The present study describes the turbulent flow characteristics of the steady flow and the combined wave-current flow for two different wave periods on unidirectional current. The turbulent kinetic energy distributions for steady flow and combined wave-current flow were analyzed to examine the turbulent energy production, pressure energy diffusion, turbulent energy dissipation and turbulent energy diffusion comprehensively. The result shows that the pressure energy diffusion drastically changes to a negative value due to the imposed surface wave on steady unidirectional current. This phenomenon indicates a low-pressure flow mode near the bed that probably affects the local sediment mobility in the coastal zone. Furthermore, the Taylor's frozen flow hypothesis was used to evaluate the dissipation rate of turbulent fluctuations to study the intermittent structure of turbulence due to imposed surface wave on steady current. Superposition of surface waves on unidirectional current significantly enhanced the finer dissipative eddies of the steady flow by the intonation of the energy cascade mechanism through wave-induced length scale.